Peningkatan Keterampilan Wirausaha Santri Dayah Modern Teungku Chik Pante Kulu Melalui Budidaya Lele dalam Ember - Bakruddin; Dewi, Cut Dara; Wulandari, Eka Sri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Dayah Terpadu Modern Teungku Chik Pante Kulu is an Islamic educational institution founded by the Teungku Chiek Pante Kulu Foundation in 2020 and started its activities in 2021. This institution is dominated by students from underprivileged families and orphans. At that time, education costs, such as tuition fees and student food costs, came from Amil Zakat, waqaf, infaq, shadaqah, as well as support from foster parents. This community service activity aims to increase students' knowledge and entrepreneurial skills through cultivating catfish in buckets, so that they are better prepared to face a better and more dignified future. The methods used in this program include socialization, delivery of material, and training which includes theoretical aspects and direct practice in the field. The results of this service show that the students' knowledge and practical skills have increased in making fish ponds from buckets, how to care for fish, providing proper food, maintaining water quality, and building the students' entrepreneurial spirit. The participants' participation in the training was very enthusiastic, providing a positive impact for the students in utilizing fish cultivation in limited areas.